Find the exact solution, in its simplest form, to the equation ln(4y + 7) = 3 + ln(2 – y) (Core Maths 3 Style Question)

First we subtract ln(2-y) from both sides to get "ln(4y+7) - ln(2-y) = 3". By applying the laws of logs from C2, we have "ln[(4y+7)/(2-y)] = 3". Therefore, if we put them as exponents of the base e, we have "eln[(4y+7)/(2-y)] = e3". By applying "lna = x means that ex = a" (from C2) , we have that "eln[(4y+7)/(2-y)] = (4y+7)/(2-y)" so we get "(4y+7)/(2-y) = e3". Next, we multiply both sides by (2-y) to get "4y+7 = e3 (2-y)". If we expand the brackets on the right side, we have "4y+7 = 2e3-ye3". By collecting all the like terms on each side - y terms on left side and the remaining terms on the right, we get "4y+ye3 = 2e3-7". Now, we factorise the left so that we have "y(4+e3) = 2e3-7". Then, we can see that we can isolate y by dividing both sides by (4+e3) and so we have "y = (2e3-7)/(4+e3)". We cannot simplify this answer further so we have reached our final answer : y = (2e3-7)/(4+e3)

Answered by Danielle B. Maths tutor

3790 Views

See similar Maths A Level tutors

Related Maths A Level answers

All answers ▸

y = x^3 ln x. Find dy/dx


Show that sqrt(27) + sqrt(192) = a*sqrt(b), where a and b are prime numbers to be determined


Express Cosx-3Sinx in form Rcos(x+a) and show that cosx-3sinx=4 has no solution MEI OCR June 2016 C4


What are the conditions for an event to be modeled with the binomial distribution?


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences